2014
DOI: 10.1016/j.arth.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Implant Fixation for Femoral Components of TKA: A Postmortem Retrieval Study

Abstract: Aseptic loosening of Total Knee Arthroplasty (TKA) components is the foremost cause of implant failure in the long term. While tibial component loosening is of primary concern, femoral loosening may become a clinical problem due to younger, more active patients seeking TKA, and also high-flexion designs. In this study, we analyzed the fixation for 19 non-revised, postmortem retrieved, femoral components of TKA with time in service ranging from 1–22 years. We found that average total contact fraction for cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…On the acetabular side the cracking in the cement mantle seems to be limited compared to the femoral counterpart and other failure mechanisms, such as debonding at the bone-cement interface, are mainly responsible for the implant loosening Wang et al, 2009;Tozzi et al, 2012). With regards to bone-cement fixation in the knee, a number of recent studies reported how the loss of interlock between bone and cement following in vivo service may eventually jeopardise the performance of both tibial Miller et al, 2014Miller et al, , 2014b and femoral (Howard et al, 2014) components over time. Goodheart et al (2014) also showed how such ex vivo loss of interlock resulted in a reduced strength of the bone-cement fixation in total knee arthroplasty (TKA).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the acetabular side the cracking in the cement mantle seems to be limited compared to the femoral counterpart and other failure mechanisms, such as debonding at the bone-cement interface, are mainly responsible for the implant loosening Wang et al, 2009;Tozzi et al, 2012). With regards to bone-cement fixation in the knee, a number of recent studies reported how the loss of interlock between bone and cement following in vivo service may eventually jeopardise the performance of both tibial Miller et al, 2014Miller et al, , 2014b and femoral (Howard et al, 2014) components over time. Goodheart et al (2014) also showed how such ex vivo loss of interlock resulted in a reduced strength of the bone-cement fixation in total knee arthroplasty (TKA).…”
Section: Introductionmentioning
confidence: 96%
“…Bone-cement interface integrity has been identified as the critical element in the success and longevity of both hip and knee cemented replacements (Gardiner & Hozack, 1994;Stocks et al, 1995;Thanner et al, 1999;Zant et al, 2008;Wang et al, 2009;Tozzi et al, 2012;Goodheart et al, 2014;Howard et al, 2014;Miller et al, 2014Miller et al, , 2014b. Principal concerns regarding the performance of cemented fixation in the hip were related to fatigue damage accumulation in the cement mantle in femoral (Cristofolini et al, 2007;Race et al, 2003Race et al, , 2011 and acetabular (Heaton-Adegbile et al, 2006;Zant et al, 2007;Tong et al, 2008) components.…”
Section: Introductionmentioning
confidence: 98%
“…Progressive radiolucencies, component migration, and pain are the clinical hallmarks of the loosening process. Recent work with postmortem retrieved knee replacements has shown that the interlock between the trabecular bone bed and poly(methyl methacrylate) (PMMA) cement does not always remain in place with in vivo use . The loss of interlock results in interfaces with more interface micromotion when loaded and results in weaker joint replacement constructs …”
mentioning
confidence: 99%
“…The mechanism driving this resorption process is not known, but stress shielding of the trabeculae, fluid flow‐induced osteolysis, monomer toxicity, and thermal necrosis have been proposed. While the amount of fixation has been described in terms of interdigitation depth and cement–bone contact fraction with in vivo service, the pattern of the trabecular resorption process has not been explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation